2021
DOI: 10.57040/asshj.v2i4.75
|View full text |Cite
|
Sign up to set email alerts
|

Public debt and economic growth: What we know today about the Nigerian economy tomorrow

Abstract: With the rising trend in Nigeria’s debt profile, this paper investigated public debt and its potential consequence on economic growth through its impact on investment. The study cut across 1981 to 2019 with data from World Bank Development Indicators (WDI) and Central Bank of Nigeria Statistical Bulletin. The Phillips-Perron unit root tested for stationarity, while the study estimated the model by adopting the Autoregressive distributed lag (ARDL) model. The long-run estimated results report that external debt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…What of maternal mortality's effect on a country's population size? Unarguably, it reduces the population size and by implication the size of the labour force which negatively affects its significant influence the country's economic growth indicator (Kur et al, 2021).…”
Section: Literature Survey 21 Economic Development and Maternal Morta...mentioning
confidence: 99%
“…What of maternal mortality's effect on a country's population size? Unarguably, it reduces the population size and by implication the size of the labour force which negatively affects its significant influence the country's economic growth indicator (Kur et al, 2021).…”
Section: Literature Survey 21 Economic Development and Maternal Morta...mentioning
confidence: 99%
“…Some of the empirical results showed that internal debt and external debt increased economic growth (Dauda et al, (2013) ;Bhatta, (2015); Khan, et al, (2016); Sanchez-Juarez & Garcia-Almada, (2016); Ogunjimi (2019); Liu &Lyu, (2020); Abdulkarim&Mohd, (2021); Upadhyaya, (2021). A few other studies showed that there is negative relationship between the public debt and economic growth (Siddique et al, (2016); Hilton, (2021); Kur et al, (2021) ;Makun, (2021).…”
Section: Introductionmentioning
confidence: 98%
“…In Sub-Saharan Africa, low-and middle-income countries saw a massive increase in debt, reaching $702 billion in 2020 [2]. In Somalia, the economy and human capital have suffered immense losses due to a prolonged civil conflict.…”
Section: Introductionmentioning
confidence: 99%